Influenza Vaccination is Associated with Lower Risk of Acute Coronary Syndrome in Elderly Patients with Chronic Kidney Disease. Issue 5 (February 2016) - Chen, Chang-I; Kao, Pai-Feng; Wu, Mei-Yi; Fang, Yu-Ann; Miser, James S.; Liu, Ju-Chi; Sung, Li-Chin
Abstract : Abstract: Elderly patients with chronic kidney disease (CKD) are at a higher risk of hospitalization for cardiovascular diseases (CVD). Previous studies have showed that influenza vaccination could reduce the risk of recurrent major cardiovascular events in patients with CVD. However, the effects of influenza vaccination on the reduction of first hospitalizations for acute coronary syndrome (ACS) in elderly patients with CKD remain unknown. We conducted a cohort study using data from the Taiwan Longitudinal Health Insurance Database 1997 to 2008. This cohort study comprised elderly patients (ages ≥55 years) with a recorded diagnosis of CKD (n = 4406) between January 1, 1999, and December 31, 2007. Each patient was followed up until the end of 2008. To minimize the selection bias of vaccine therapy, a propensity score adjustment was applied. The hazard ratio (HR) and 95% confidence interval (CI) for the association between the influenza vaccination and the occurrence of first hospitalization for ACS was evaluated by Cox proportional hazards regression. We further categorized the patients into 4 groups according to their vaccination status (unvaccinated, and total number of vaccinations: 1, 2–3, and ≥4). We found that elderly CKD patients without prior CVD history receiving influenza vaccination exhibited a lower risk of hospitalization for ACS (adjusted HR = 0.35, 95% CI 0.30–0.42; P < 0.001). We observed consistent protective effects regardless of age groups (55–64, 65–74, and ≥75), gender, and seasonality of influenza. When the patients were stratified according to the total number of vaccinations, the adjusted HRs for first ACS hospitalization were 0.62 (95% CI 0.52–0.81), 0.35 (95% CI 0.28–0.45), and 0.13 (95% CI 0.09–0.19) for patients who received 1, 2 to 3, and ≥4 vaccinations. There was a significant trend of decreasing risk of ACS hospitalization with an increasing number of vaccinations. The results of our observational study could strengthen the annual vaccination policy and physicians should be aware of missed opportunities to vaccinate elderly patients with CKD against influenza. The potential public health impact of influenza vaccination, particularly in the elderly CKD patients without a history of CVD, who are at risk for ACS, should be further explored.